Resolution of the Pennsylvania Committee on Safety, Oct. 27, 1775, Col. Rec. Penn. 10:383. - (:unkn) unknown (My University, 1775)
Requiring that all muskets be "proved" prior to purchase
Keywords: MANUFACTURE ONLY